Kebijakan Moneter Dan Perkembangan Ekonomi: Perspektif Islam - Aulia Fitri Anggraini; Dinda Salsabila Sarly; Wahyu Rama Wirayuda (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
The government's role in Islamic economics is very significant, not only in regulating public aspects in accordance with Islamic principles, but also in financial matters such as managing basic needs, creating jobs, and maintaining the stability of the value of money. Public authorities need appropriate arrangements to steer the economy in the desired direction. One of the strategies used is financial regulation, which aims to control the money supply so that economic growth is stable, the cost of living is affordable, and jobs are available. This research aims to explore how the financial approach works from an Islamic perspective in depth. In the context of Islamic economics, the task of public authorities is to ensure that Islamic principles apply in terms of free income, interest-free economy, and money management in accordance with Islamic principles. Financial regulatory instruments also go beyond the use of open markets and custody of money, including in terms of distribution of credit, proportion of advances, and benefits in accordance with Islamic rules. This journal explores the relationship between monetary policy and economic development from an Islamic perspective. The focus is on the government's role in regulating monetary policy to achieve stable and sustainable economic growth in accordance with Islamic principles. The discussion includes financial management strategies that include controlling the money supply, stability of the value of money, and development of an interest-free economy. By considering the basis of free income in Islamic economics, this journal also highlights monetary policy instruments that are in accordance with Islamic values, such as credit distribution and benefit proportions that follow Islamic rules. This research aims to provide in-depth insight into how monetary policy can be implemented effectively in the context of Islamic economics, as well as implications and suggestions for sustainable economic development from an Islamic perspective.